Peranan Dinas Pariwisata Kabupaten Badung Dalam Mengembangkan Potensi Pariwisata Badung - Adnyani Asak, K. Shanti; Sirtha, I Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
The island of Bali is an island that is rich enough to attractions both natural attractionsand cultural sights. One of the area in Bali which has the potential’s tourism is Badung regency.In developing tourism potential,Badung Government especially Tourism Department in chargeof the management of tourism in Badung regency. Therefore, this paper will describe what is thetourism destination potential that needs to be developed in tourism and how the delinquentBadung Tourism Office to developing tourism in the region.this paper use empirical legalresearch.The conclusions is some of the objects that need to be developed are the area PuraPucak Tedung, Pura Sada Kapal, Agro Tourism Plaga, Baha Tourism Village. One attemptBadung Tourism Department to improve security by installing CCTV and increased supervisionby security guards, and in addition the Department of Tourism plays a role for promotingtourism within and outside the country and develop human resources by conducting trainings inthe field of tourism.
Keywords: Authority, Tourism Potential, Tourism Destination